Suppression of parasitic lasing in erbium doped thin film lithium niobate waveguide amplifier by integrated wavelength division multiplexer - Jinli Han; Mengqi Li; Qiaonan Dong; Rongbo Wu; Zhe Wang; Zhaoxiang Liu; Saisai Sun; Zhiwei Fang; Min Wang; Haisu Zhang; Ya Cheng (APL Photonics)
Photonic integrated circuits based erbium doped amplifiers have attracted great interest due to their compact footprint, high gain in the telecom C-band, and high scalability for functional integration. In this work, a wavelength division multiplexer integrated erbium doped waveguide amplifier fabricated on the thin film lithium niobate on insulator platform is demonstrated. An on-chip saturated power of 10 dBm with the net gain around 10 dB is achieved from the monolithically integrated amplifier chip with the footprint of only 3 × 5 mm2. In particular, the suppression of parasitic lasing in the waveguide amplifier is realized thanks to the spectral response of the integrated wavelength division multiplexer. Theoretical analysis of parasitic lasing on amplifier performance is also conducted. The demonstrated integrated erbium doped waveguide amplifier will find great use in various applications based on the thin film lithium niobate on an insulator platform.